PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADADP KEPUASAN KONSUMEN PADA WAROENG STEAK & SHAKE MELATI PEKANBARU - Rismawati S, Asina; Karneli, Okta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted at Waroeng Steak & Shake Melati Pekanbaru. The problem in this research is declined the number of transactions and declined number of sales within the last 5 years. This study aims to determine the effect of brand image and product quality on customer satisfaction at Waroeng Steak & Shake Melati Pekanbaru. In this research data analysis used descriptive and quantitative with SPSS program. The sample in this research totalled 100 respondents, with sampling method using a purposive sampling. Data collection techniques used are primary and secondary data through observation, interview, and questionnaire. Methods of data analysis used a simple linear regression analysis method and multiple linear regression From the results of tests conducted indicate that the brand image and product quality have a positive and significant impact on customer satisfaction in Waroeng Steak & Shake Melati Pekanbaru. Keywords: Brand Image, Product Quality and Consumer Satisfaction.